1991
DOI: 10.1007/bf00037063
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast transcription is required to express the nuclear genes rbcS and cab. Plastid DNA copy number is regulated independently

Abstract: RbcL and rbcS mRNA levels and plastid transcription activity are low in the basal meristematic region of barley primary leaves and increase coordinately during leaf cell development with a similar time course in dark-grown or illuminated seedlings. The capacity of light to cause cab mRNA accumulation shows a similar dependence on leaf cell development. These results indicate that the initial activation of chloroplast gene expression and the expression of some nuclear genes encoding plastid proteins are coupled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 52 publications
3
60
0
Order By: Relevance
“…This explanation is feasible since photobleaching requires chlorophyll function, and thus the initiation of chloroplast biogenesis, the rates of synthesis, and the stability of chloroplast transcripts can vary greatly among genes or among developmental stages (Deng and Gruissem, 1987;Kuchka et al, 1989;Ngernprasirtsiri et al, 1990;Klaff and Gruissem, 1991;Rapp and Mullet, 1991;Rapp et al, 1992). An alternative explanation for our RBCL results is that gun mutants maintain a low level of chloroplast transcription, despite photobleaching, that may be sufficient for RBCL transcript accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This explanation is feasible since photobleaching requires chlorophyll function, and thus the initiation of chloroplast biogenesis, the rates of synthesis, and the stability of chloroplast transcripts can vary greatly among genes or among developmental stages (Deng and Gruissem, 1987;Kuchka et al, 1989;Ngernprasirtsiri et al, 1990;Klaff and Gruissem, 1991;Rapp and Mullet, 1991;Rapp et al, 1992). An alternative explanation for our RBCL results is that gun mutants maintain a low level of chloroplast transcription, despite photobleaching, that may be sufficient for RBCL transcript accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of nuclear-encoded transcripts for nitrate reductase and hydroxypyruvate reductase is also sensitive to photobleaching, even though they encode nonchloroplast proteins with functions related to photosynthesis (OelmDller and Briggs, 1990;Schwartz et al, 1991). In other studies, nitrogen starvation or the inhibition of plastid transcription or translation from the time of germination blocks CAB messenger RNA (mRNA) accumulation (Oelmiiller et al, 1986;Taylor et al, 1987;Plumley and Schmidt, 1989;Taylor, 1989;Mathews and Durbin, 1990;Rapp and Mullet, 1991). In contrast, less severe chloroplast lesions, such asachlorophyll biosyntheticdeficiency or a chloroplast translational block in green plants, do not block CAB expression (Harpster et al, 1984;Oelmiiller et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitor experiments with chloramphenicol showed that plastid protein synthesis is not required for the generation of the plastid factor (Oelmiiller et al, 1986b;Hess et al, 1994). By contrast, treatment of leaves from barley and other plant species with tagetitoxin, an inhibitor of prokaryotic-type RNA polymerases (Mathews and Durbin, 1990), completely blocked accumulation of rbcS and lhcb, but not of actin transcripts (Rapp and Mullet, 1991). Plastid transcription, but not plastid protein synthesis, thus seems to be necessary for the specific expression of nuclear genes during the early stages of chloroplast development.…”
Section: Morphological Cellular and Molecular Events During The Ligmentioning
confidence: 98%
“…Treatment of barley seedlings with tagetitoxin resulted in decreased transcripts of the RbcS and Lhcb1 gene families, but did not affect plastid DNA replication (Rapp & Mullet 1991). Nalidixic acid, a prokarotic DNA gyrase inhibitor that affects plastid .…”
Section: Inhibitors Of Plastid Gene Expression and Plastid-ribosome Dmentioning
confidence: 99%